2023
DOI: 10.1371/journal.pone.0292321
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motivational and instructional self-talk on attentional control under noise distraction

Liu Yang,
Yingchun Wang

Abstract: Inhibition is the key factor of attentional control (AC). Basketball players are typically exposed to noise from the audience or opposing teams while competing. These distractions disrupt the attentional systems, ultimately compromise the athletes’ inhibition ability and directly affect their performance on the court. Hence, effective AC strategies are crucial. Two studies were demonstrated to investigate the effects of noise distractions on attentional control and the moderating effect of self-talk. In Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…For instance, a study by Galanis and Hatzigeorgiadis revealed that, despite 6 weeks of shooting training, there was a significant reduction in shooting accuracy when athletes were subjected to noise distractions as compared to baseline levels where no such distraction was present ( 6 ). According to Attentional Control Theory (ACT), auditory noise disrupts attentional control processes, making it difficult to focus on the task at hand ( 7 , 8 ). This disruption compromises athletes’ attentional control ability, hindering their concentration on movements or strategies during competitions, and ultimately results in poorer performance ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study by Galanis and Hatzigeorgiadis revealed that, despite 6 weeks of shooting training, there was a significant reduction in shooting accuracy when athletes were subjected to noise distractions as compared to baseline levels where no such distraction was present ( 6 ). According to Attentional Control Theory (ACT), auditory noise disrupts attentional control processes, making it difficult to focus on the task at hand ( 7 , 8 ). This disruption compromises athletes’ attentional control ability, hindering their concentration on movements or strategies during competitions, and ultimately results in poorer performance ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Attentional Control Theory (ACT), auditory noise disrupts attentional control processes, making it difficult to focus on the task at hand ( 7 , 8 ). This disruption compromises athletes’ attentional control ability, hindering their concentration on movements or strategies during competitions, and ultimately results in poorer performance ( 8 ). The degree of disruption is further exacerbated by the unpredictability and variability of the noise.…”
Section: Introductionmentioning
confidence: 99%
“…Однак, механізм, за допомогою якого відбувається вплив на оброб-ку інформації, в тому числі у практиці фізичної культури і спорту, є джерелом багатьох дискусій. Більшість існуючих досліджень вивчали лише вплив інтенсивності (величини) на продуктивність, хоча результати були здебільшого неоднозначними [15]. До прикладу, результати досліджень D. E. Broadbent свідчать, що викликати стрес дією звуку можна лише через особливо чутливі завдання, тобто тривалого впливу із дуже високою або дуже низькою швидкістю подання інформації [6].…”
unclassified